Why the honey badger don't care: Convergent evolution of venom-targeted nicotinic acetylcholine receptors in mammals that survive venomous snake bites. (1st June 2015) - Drabeck, Danielle H.; Dean, Antony M.; Jansa, Sharon A.
Abstract: Honey badgers ( Mellivora capensis ) prey upon and survive bites from venomous snakes (Family: Elapidae), but the molecular basis of their venom resistance is unknown. The muscular nicotinic cholinergic receptor (nAChR), targeted by snake α-neurotoxins, has evolved in some venom-resistant mammals to no longer bind these toxins. Through phylogenetic analysis of mammalian nAChR sequences, we show that honey badgers, hedgehogs, and pigs have independently acquired functionally equivalent amino acid replacements in the toxin-binding site of this receptor. These convergent amino acid changes impede toxin binding by introducing a positively charged amino acid in place of an uncharged aromatic residue. In venom-resistant mongooses, different replacements at these same sites are glycosylated, which is thought to disrupt binding through steric effects. Thus, it appears that resistance to snake venom α-neurotoxin has evolved at least four times among mammals through two distinct biochemical mechanisms operating at the same sites on the same receptor. Highlights: We investigate the molecular basis of resistance to elapid venoms in honey badgers. We used a phylogenetic approach to infer the molecular evolution of nAChR for a wide range of mammals. Resistance to snake venom α-neurotoxin has evolved at least four times among mammals. Honey badgers, hedgehogs, and pigs have nearly equivalent amino acid replacements. Two distinct biochemical mechanisms confer α-neurotoxin resistance on mammal nAChRs.